Use of double J stent in a case of spontaneous ureteral extravasation of urine - (:unkn) unknown (My University, 2000)
OBJECTIVES: Although there are numerous case reports of spontaneous rupture of the collecting system, especially including the calyceal fornix or the renal pelvis, spontaneous rupture of the ureter is a rare condition. METHODS: Herein, we present a case of a patient who suffered symptoms of acute abdomen due to rupture of the proximal ureter. Extensive assessment revealed no etiological factor as to the extravasation. RESULTS/CONCLUSIONS: The condition was managed conservatively by insertion of a double-J catheter. The double-J ureteral stent was removed on the first postoperative month under local anesthesia uneventfully. One year after the spontaneous ureteral extravasation, the patient remained without clinical problems. The diagnosis, pathogenesis and complications of this unusual condition are reviewed.
Keywords: Humans; Equipment Design; Stents; Urine; Ureteral Diseases